Determination of Volatiles in Flue-Cured Tobacco by Gas Chromatography–Mass Spectrometry (GC–MS) with Chemometrics. (13th June 2022) - Qi, Dawei; Zhou, Yan; Wang, Jiale; Fei, Ting; Wu, Da; Lu, Jie
Abstract: This study reports the utilization of two-step headspace (HS) to profile the volatile compounds of flue-cured tobacco. The relationship between the volatile components and geographic origin was investigated using multivariate data analysis. To avoid the impact of adsorption caused by tobacco on the HS extraction, the tobacco was soaked by saturated NaCl solutions prior to the HS sampling. However, the introduction of water vapor may affect the subsequent gas chromatography–mass spectrometry (GC–MS) analysis. Thus, two-step HS, which is based on the coupling of the programmed temperature vaporizer inlet and HS autosampler, was employed to remove the water vapor while simultaneously preconcentrating the volatile compounds. The repeatability and stability were evaluated, and 80 compounds were identified from 25 flue-cured tobacco samples. Both principal component analysis (PCA) and hierarchical clustering analysis (HCA) revealed that the volatile components of flue-cured tobacco were closely related to the geographic origin. Furthermore, the characteristic volatiles of the flue-cured tobacco from different regions were illustrated using partial least squares discriminant analysis (PLS-DA). The presented work provided a simple and reliable way to profile the volatile components and characterize geographic origin of tobacco and tobacco products.